Photobleaching alters the morphometric analysis of fluorescently labeled neurons and microglial cells - Tamás F. Polgár; Tamás F. Polgár; Krisztina Spisák; Krisztina Spisák; Zalán Kádár; Nora Alodah; Gabor J. Szebeni; Kata Klein; Roland Patai; László Siklós; Bernát Nógrádi; Bernát Nógrádi (Pathology and Oncology Research)
Photobleaching of immunofluorescence signal is a well-known phenomenon, however, its impact on derived parameters characterizing number and shape of different cell types in tissue sections is less understood. Our aim was to determine whether the duration of illumination and the type of fluorophore (Alexa Fluor 546 (A546), and Alexa Fluor 488 Plus (A488)) can influence the acquired morphometric parameters of cells in the nervous system. Immunofluorescent staining of microglia and neurons was performed on mouse spinal cord sections. Mean color intensity in a field of view, number of detectable neuronal cell profiles, partial coverage of microglial profiles, and fractal geometrical parameters were determined. All measurements were made using epifluorescence microscopy with identical acquisition parameters. Most of the measured parameters suffered significant alternation after 30–60 s of illumination. The data-altering effect of photobleaching was most prominent in the case of mean fluorescent intensity. Thus, while immunofluorescent staining is useful for co-localizing different groups of cells, cell-specific quantitative morphological measurements require photostable staining. Possibility of the combination of these methods on the same section in order to achieve multi-channel localization without photobleaching is exemplified.